Hydrophobicity and non-thrombogenicity of nanoscale dual rough surface coated with fluorine-incorporated diamond-like carbon films: Biomimetic surface for blood-contacting medical devices - Hasebe, Terumitsu; Nagashima, So; Kamijo, Aki; Moon, Myoung-Woon; Kashiwagi, Yousuke; Hotta, Atsushi; Lee, Kwang-Ryeol; Takahashi, Koki; Yamagami, Takuji; Suzuki, Tetsuya (ELSEVIER SCIENCE SA, 2013)
We investigated the hydrophobicity and non-thrombogenicity of a nanoscale dual rough surface coated with hydrophobic and non-thrombogenic fluorine-incorporated diamond-like carbon (F-DLC) films. We prepared Si (1 0 0) and a dual rough surface composed of coarse posts and nano-sized fine posts as substrates. DLC film was deposited on the Si substrate, and F-DLC film was deposited on Si or the dual rough surface using radio frequency plasma enhanced chemical vapor deposition method. The surface hydrophobicity of each sample was examined with water contact angle measurements and the non-thrombogenicity was evaluated through incubation with platelet-rich plasma isolated from human whole blood. The water repellency was dramatically improved on the F-DLC-coated dual rough surface compared with that on DLC-coated Si or F-DLC-coated Si, which had a water contact angle of 130.6 degrees. There was no significant difference in the values for the platelet-covered area between DLC-coated Si and the F-DLC-coated dual rough surface. As DLC is being considered for widespread clinical use as a surface coating for medical devices owing to its non-thrombogenicity compared with other biomaterials, the F-DLC-coated dual rough surface presented in this study still has the potential for clinical use, such as temporary blood-contacting medical devices, to take advantage of its high hydrophobicity. (c) 2013 Elsevier B.V. All rights reserved.
Keywords: PLATELET-ADHESION; PROTEIN ADSORPTION; SUPERHYDROPHOBIC SURFACES; ACTIVATION; COATINGS; DLC; DEPOSITION; TIN